Dual role of Fam208a during zygotic cleavage and early embryonic development - Gresakova, Veronika; Novosadova, Vendula; Prochazkova, Michaela; Prochazka, Jan; Sedlacek, Radislav (Experimental cell research, 2021)
Maintenance of genome stability is essential for every living cell as genetic information is repeatedly challenged during DNA replication in each cell division event. Errors, defects, delays, and mistakes that arise during mitosis or meiosis lead to an activation of DNA repair processes and in case of their failure, programmed cell death, i.e. apoptosis, could be initiated. Fam208a is a protein whose importance in heterochromatin maintenance has been described recently. In this work, we describe the crucial role of Fam208a in sustaining genome stability during cellular division. The targeted depletion of Fam208a in mice using CRISPR/Cas9 led to embryonic lethality before E12.5. We also used the siRNA approach to downregulate Fam208a in zygotes to avoid the influence of maternal RNA in the early stages of development. This early downregulation increased arresting of the embryonal development at the two-cell stage and the occurrence of multipolar spindles formation. To investigate this further, we used the yeast two-hybrid (Y2H) system and identified new putative interaction partners Gpsm2, Svil, and Itgb3bp. Their co-expression with Fam208a was assessed by RT-qPCR profiling and in situ hybridization [1] in multiple murine tissues. Based on these results we proposed that Fam208a functions within the HUSH complex by interaction with Mphosph8 as these proteins are not only able to physically interact but also co-localise. We are bringing new evidence that Fam208a is a multi-interacting protein affecting genome stability on the cell division level at the earliest stages of development and by interaction with methylation complex in adult tissues. In addition to its epigenetic functions, Fam208a appears to have an important role in the zygotic division, possibly via interaction with newly identified putative partners Gpsm2, Svil, and Itgb3bp.
Keywords: Animals; Nuclear Proteins; Fam208a; Multipolar spindle apparatus; Female; fosfoproteiny; CRISPR-Cas systémy; jaderné proteiny; Genomic Instability; ženské pohlaví; Mice, Knockout; CRISPR-Cas Systems; myši knockoutované; Zygote; zygota; Phosphoproteins; Mice; těhotenství; metylace DNA; myši; Mitosis; mitóza; epigeneze genetická; Male; HUSH; Embryonic Development; DNA Methylation; nestabilita genomu; zvířata; embryonální vývoj; mužské pohlaví; Mice, Inbred C57BL; Pregnancy; Epigenesis, Genetic; myši inbrední C57BL; Genome stability